On the Origin of Damped Electrochemical Oscillations at Silicon Anodes (Revisited). Issue 14 (27th August 2014) - Proost, Joris; Blaffart, Frédéric; Turner, Stuart; Idrissi, Hosni
Abstract Electrochemical oscillations accompanying the formation of anodic silica have been shown in the past to be correlated with rather abrupt changes in the mechanical stress state of the silica film, commonly associated with some kind of fracture or porosification of the oxide. To advance the understanding on the origin of such oscillations in fluoride‐free electrolytes, we have revisited a seminal experiment reported by Lehmann almost two decades ago. We thereby demonstrate that the oscillations are not stress‐induced, and do not originate from a morphological transformation of the oxide in the course of anodisation. Alternatively, the mechanical features accompanying the oscillations can be explained by a partial relaxation of the field‐induced electrostrictive stress. Furthermore, our observations suggest that the oscillation mechanism more likely results from a periodic depolarisation of the anodic silica.